Pendampingan Pastoral Kepada Anak Korban Pelecehan Seksual - Christine Lois Hadi Waluyo (AISTHETIKOS Jurnal Ilmu Teologi dan Seni, 2025)
This research is motivated by the findings from observations, there is a child who experienced sexual abuse. This then encourages researchers to find out more about the situation experienced by the child. From the results of the study showed the abuse experienced by the child. Therefore the research was formulated that how to provide pastoral assistance to child victims of sexual abuse. The purpose of this research is to describe and analyze children who are victims of sexual harassment. This study used qualitative methods and an integrative approach and was collected using observation and pastoral counseling techniques.